Peer-Based Learning as a Method of Enhancing the Problem-Solving Performance of Marine Transportation Students - Mario D. Natividad; Virginia Natividad-Franco (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The study aimed to evaluate the effect of peer-based learning on the problem-solving skills of students in marine transportation, providing evidence-based suggestions for the development of maritime curricula. During the second semester of the 2024–2025 academic year, 80 third-year students enrolled in SEAM 6 (Trim, Stability, and Stress of a Vessel) at the College of Maritime Education, Dr. Yanga’s Colleges, Inc., participated in the true experimental design. Participants were randomly assigned to either a peer-based learning group or a conventional individual learning group. Validated problem-solving activities were employed to collect data, and t-tests were used in the statistical analysis to identify performance differences between groups. Results showed that students who engaged in peer-based learning consistently performed better than those in the traditional learning group, as seen by their noticeably higher exercise scores, according to the data. The t-test results highlighted the practical value of the findings by confirming statistical significance and demonstrating a significant effect size. A training program was created in response to these findings to encourage the incorporation of peer-based teaching techniques in skill-based marine courses. These findings provide empirical evidence for the implementation of cooperative learning methodologies in maritime training programs, demonstrating their effectiveness in technical education. By highlighting how peer engagement improves student comprehension, skill development, and overall competency, the study advances educational philosophy. Practically, peer-based learning can promote improved performance in technical topics and a deeper grasp of the material. Future research is recommended to investigate the impact of peer-based learning on information retention.